The Influence of Digital Talent Management on Enhancing Employee Innovation in Endowment Fund Management Institutions: A Case Study at the Indonesian Endowment Fund for Education - Adam Rachmat; Anggraini Sukmawati; Arry Ekananta (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study examines the influence of digital talent management on enhancing innovative work behavior among employees at the Indonesia Endowment Fund for Education (LPDP), a key institution under the Ministry of Finance that manages education endowment funds. The research has three main objectives: 1) to identify the characteristics of digital talent at LPDP, 2) to analyze the influence of digital talent management, digital leadership, digital competence, and digital culture on innovative work behavior, and 3) to formulate managerial recommendations for developing digital talent management strategies. This study adopts a quantitative approach. Data were collected from 167 LPDP employees across four directorates who completed the questionnaire. The data were gathered through a structured online survey and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results indicate that digital talent management significantly influences innovative work behavior, both directly and indirectly through mediating factors such as digital competence, digital leadership, and digital culture. Digital competence and digital leadership have particularly strong effects, while digital culture reinforces a work environment that is conducive to innovation. The managerial implications of these findings include the need to strengthen career development pathways, improve performance evaluation and compensation systems, and foster a digital culture that promotes collaboration and risk-taking. In conclusion, enhancing innovation among public sector employees requires a strategic and comprehensive approach to digital talent management that aligns with the institution’s vision of preparing globally competitive human resources and promoting national innovation.